Climate Smart Agriculture (CSA) Handbook - Centre for Coordination of Agricultural Research and Development for Southern Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This Climate Smart Agriculture (CSA) handbook has been developed as a resource material for use by CSA practitioners in providing training, policy advocacy, and upscaling CSA technologies and practices for improving sustainable productivity, adapting to the effects of climate change, and mitigating climate change. The handbook is structured in a manner that covers key aspects of climate-smart agriculture, CSA working definition, including the effects of climate change, CSA technologies for increasing productivity, enhancing adaptation and resilience, mitigation, considerations for clean energy and the scaling up of CSA technologies have been. Respective chapters have covered issues of productivity, adaptation/resilience, mitigation and clean energy sources, and best bets suitable for supporting SADC countries' food and sustainable development ambition. The choice of best bets was based on observed evidence so far on how effective the CSA technologies and practices address the three pillars of CSA, given the experiences acquired from the countries of the SADC region over time.